Parametric Study of Rider’s Comfort in a Vehicle with Semi-Active Suspension System Under Steady State Conditions - Arinola Bola Ajayi; Sunday Joushua Ojolo; Ediketin Ojogho; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
Due to the influence of road roughness on all quantities representing dynamic response of vehicles such as vehicle ride comfort, tire dynamic force, dampers and spring forces, etc., the interaction between a vehicle and road profiles in relation to the comfort and health of passengers has become significant as road roughness causes a spectrum of oscillations for a moving vehicle. Thus, this study investigates the dynamic response of semi-active vehicle suspension system under the influence of steady state road conditions such as smooth, gravel and suburban roads to obtain mathematical equations based on the pitch and heave motions of the vehicle. Power spectral density, PSD, was used to characterize the road input spectrum on the basis of the road roughness parameters which correlate with International Roughness Index, (IRI). Vehicle suspension system responses to the different road inputs were obtained by simulation based on the mathematical model developed using Matlab/Simulink software. The root-mean-square acceleration was used as objective metric to estimate the passenger’s discomfort, dynamic tire force and suspension travel at a constant vehicle speed of 20 km/h while the ISO 2631 was applied to predict the discomfort experienced by the riders under different steady state road irregularities. The discomfort experienced by the riders on the gravel road and suburban road increased when the vehicle parameters were increased and also when the speed of the vehicle was increased. For smooth road, the riders experienced comfort according to ISO 2631, although the discomfort threshold increased with increase in speed of the vehicle but still within the threshold of human comfort zone. It can be concluded that for a vehicle ride within the human comfort zone on gravel and suburban roads, the speed of the vehicle should be brought down considerable below 20 km/h and the suspension systems should also be improved upon.